2019
DOI: 10.26444/aaem/104666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environment on residence and selected demographic and clinical parameters of preschool children with IgE-dependent asthma

Abstract: Introduction and objective. An important role in the pathogenesis of asthma in children is played by individual parameters and environmental factors, in particular, those related to the place of residence. The aim of this study was to assess the impact of the living environment on the basic demographic and clinical parameters of preschool children with IgE-dependent asthma Materials and method. 176 children (126 from urban and 52 from rural areas) aged 5.22±0.34 years, with newly-diagnosed IgE-dependent asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is also possible that migraines are not directly caused by asthma; shared environmental triggers may be responsible for the association between them. Studies have shown that air pollution, such as high concentrations of PM2.5, PM10, and NO 2 , can induce asthma and even aggravate its symptoms ( 37 ). Similarly, the rate of emergency treatments for migraines increases due to exposure to air pollution ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that migraines are not directly caused by asthma; shared environmental triggers may be responsible for the association between them. Studies have shown that air pollution, such as high concentrations of PM2.5, PM10, and NO 2 , can induce asthma and even aggravate its symptoms ( 37 ). Similarly, the rate of emergency treatments for migraines increases due to exposure to air pollution ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The exaggerated response of host immune systems to foreign antigens is a main cause of asthma/ALS. Allergens exposure may lead to the excessive IgE production and cellular responses, a trigger of asthma/ALS attack [10]. Hence, identification and avoidance of the prevalent allergens is helpful for the prevention and treatment of asthma/ALS.…”
Section: Discusssionmentioning
confidence: 99%
“…According to the WHO, allergic asthma -an immunemediated disease -ranks among the most common chronic medical conditions, affecting approximately 4% of the global population and 10% of Europeans [15,16]. The Global Initiative for Asthma report estimated the prevalence of asthma in various countries at 1% -18% of the population [16]. The ISAAC study found that asthma is more common in developed countries, while in developing countries it is more severe in children.…”
Section: Introductionmentioning
confidence: 99%